Evaluation of serum levels of IL-6 and adiponectin in COVID-19 patients and their relationship with disease severity - Marzieh Norouzian; Khojasteh Sharifi-Sarasiabi; Majid Najafi-Asl; M. Hassani Azad; H. Estabraghnia Babaki (Инфекция и иммунитет, 2022)
Background. The SARS-CoV-2 pandemic has prompted researchers around the world to identify risk factors associated with disease severity and mortality. Results suggest that COVID-19 mortality might be due to a cytokine storm involving IL-6, and that obesity can be considered a risk factor for COVID-19 prevalence, severity, and mortality. The current study aimed to evaluate the serum levels of IL-6 and adiponectin in patients and their relationship with disease progression. Materials and methods. ELISA was used to assess the levels of IL-6 and adiponectin in serum samples from a control group and from patients with COVID-19 at the time of admission to ICU or non-ICU wards. The results were analyzed using the MannWhitney and Spearman tests. Results. Mean serum levels of adiponectin in patients admitted to ICU (10.1815.4 ng/ml) were significantly higher than patients admitted to non-ICU wards (3.143 ng/ml, p = 0.001). Mean serum IL-6 levels showed a similar pattern, however the difference was not statistically significant (p = 0.18). In addition, a significant direct correlation was observed between adiponectin expression and IL-6 (R = 0.2, p = 0.03). Conclusion. The results of this study show that serum levels of adiponectin in COVID-19 patients with severe lung involvement were significantly higher than those with less lung involvement. This finding is of high importance mainly due to the critical role of the lungs in adiponectin signaling, and as a result, adiponectin disorders may be associated with pulmonary complications in COVID-19 patients.